The expression of MC4Rs in D1R neurons regulates food intake and locomotor sensitization to cocaine. (17th July 2013) - Cui, H.; Lutter, M.
Abstract : While it is known that mice lacking melanocortin 4 receptor (MC4R) expression develop hyperphagia resulting in early‐onset obesity, the specific neural circuits that mediate this process remain unclear. Here, we report that selective restoration of MC4R expression within dopamine‐1 receptor‐expressing neurons [MC4R/dopamine 1 receptor (D1R) mice] partially blunts the severe obesity seen in MC4R‐null mice by decreasing meal size, but not meal frequency, in the dark cycle. We also report that both acute cocaine‐induced anorexia and the development of locomotor sensitization to repeated administration of cocaine are blunted in MC4R‐null mice and normalized in MC4R/D1R mice. Neuronal retrograde tracing identifies the lateral hypothalamic area as the primary target of MC4R‐expressing neurons in the nucleus accumbens. Biochemical studies in the ventral striatum show that phosphorylation of DARPP‐32 Thr ‐34 and GluR1 Ser ‐845 is diminished in MC4R‐null mice after chronic cocaine administration but rescued in MC4R/D1R mice. These findings highlight a physiological role of MC4R‐mediated signaling within D1R neurons in the long‐term regulation of energy balance and behavioral responses to cocaine. Abstract : The expression of MC4Rs in D1R neurons suppresses food intake and body weight gain and mediates cocaine‐induced locomotor sensitization.